HOUSING POLICY DYNAMICS: CAN THE GOVERNMENT MEET HOUSING NEEDS FOR LOW-INCOME COMMUNITIES? - Wardana, Data; Ismail, Solahuddin; Wijaya, Mendra; Syafhendry, Syafhendry (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
This article seeks to identify government housing policies for low-income individuals (MBR). The existence of disparities between Housing and Residential Areas Law No. 1 of 2011 and Regional Government Law No. 23 of 2014 regarding the authority of local governments to implement housing and residential area affairs has implications for meeting housing needs, particularly housing for low-income people (MBR). The issue centered on the limitations of the regional authority in instituting MBR housing. This article employs a qualitative methodology involving document analysis, secondary data from government and local government sources, and library research to bolster housing and residential area research. This study concludes that the need for regional authority in implementing MBR housing development significantly impacts regional housing development. For local governments to contribute to the development of MBR housing in licensing and non-licensing fields, the government issued a policy package and various regulations related to the acceleration of housing development and permits for housing construction. Nonetheless, this policy should have been more effective. Financing the housing development program through a Public-Private Partnership (KPBU) is an additional option.gb777